Application of the eHealth literacy in digital health management - Sobolieva-Tereshchenko, Olena; Zhukova, Yuliia (Management and Entrepreneurship: Trends of Development, 2023)
The state policy in Ukraine regarding the informatization of the healthcare system, as well as the introduction of the latest information technologies, is aimed at eliminating the backlog in this area from the leading countries of the world and accelerating entry into the information space of the international community. It is currently impossible to bring Digital Health Management (DHM), practical medicine, medical education, and health science to the modern level without the use of theoretical knowledge. The study provides a conceptual framework for the development and use of eHealth literacy in DHM, as well as in national and international eHealth management activities. The purpose of this study is to explore the application of eHealth literacy instruments for assessment and implementation in DHM. Methodology: The study used a systematic review and analysis of articles published (from 2006 to 2022) in PubMed, Web of Science, and Scopus. The systematic review was conducted in accordance with PRISMA principles. The manual search strategy was used for the study. The methodological quality of each validation study was assessed using the COSMIN checklist and extracted data from the study. The research findings show that most of these instruments are only for planning and evaluating the results of medical interventions and for improving the skills of health professionals. However, existing eHealth Literacy instruments do not contain items of digital finance that could accelerate the integration of digital financial literacy into the health sector. Eight qualitative studies of eHealth literacy instruments were found useful for evaluation or implementation in DHM. JEL Classification: G28, I18, H51